Aliran Tafsir Tabi'in di Madinah - Taufik CH; Adha Saputra; Alber Oki (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2020)
The purpose of this study is to determine the flow of tabi'in interpretation in Medina. This research uses a qualitative approach and literature review method. Based on the results of the study, The madrasa of interpretation in Medina was pioneered by Ubay ibn Ka'b (d. 20 H). In Medina at that time there were many companions who did not move to other Islamic regions, and preferred to teach the Qur'an and Sunnah to their followers. Thus, there was a madrasa of interpretation in Medina where the famous tabi'in mufassir learned. The three most famous mufassir tabi'in are Zaid ibn Aslam (d 136 H), Abu 'Aliyah (d 93 H), and Muhammad ibn ka'b al-Qarazi (d 120 H).